Integrating Business Model Canvas and Balanced Scorecard for Porang Tuber Business Development: A Case Study of Koperasi Porang Garut Agro - Raihanah Yurizka Kinanti; Yooce Yustiana; Rizkita Rachmi Esyanti (Caraka Tani: Journal of Sustainable Agriculture, 2026)
Indonesia is expected to face a decline in rice harvest areas in 2024, which threatens national food security and highlights the need for alternative food sources from local commodities such as Amorphophallus muelleri (porang). Koperasi Porang Garut Agro (KPGA), a community-based cooperative in Garut Regency, has the potential but still struggles with supply stability, logistics, and institutional capacity. This study formulates a business management strategy for KPGA by integrating the Business Model Canvas (BMC) with the Balanced Scorecard (BSC). Data were collected through interviews, field observations, and document reviews, then analyzed using descriptive quantitative methods to assess tuber availability and distribution, complemented by financial feasibility analysis. The business model was developed through SWOT-BMC analysis and then mapped into the 4 perspectives of the BSC to design appropriate management strategies. The results indicate that porang availability in Garut is sufficient for KPGA’s operations, although price fluctuations and unequal profit distribution persist. Additionally, financial analysis suggests that KPGA’s operations are feasible but have not yet achieved optimal returns. To address these challenges, integration of the BMC and BSC produced 13 core strategies focusing on improving product quality and standards, developing processed products, enhancing human resource competencies, strengthening distribution and storage efficiency, expanding market segments, and improving financial management and support for farmers. These strategies offer a clear roadmap for enhancing KPGA’s competitiveness and supporting Indonesia’s broader goal of sustainable food diversification.